The evaluation of surgical treatment outcomes of low and high-energy pelvic fractures using ilio-iliac plate fixation - Wojciech Iluk; Daniel Kotrych (Chirurgia Narządów Ruchu i Ortopedia Polska)
A retrospective study of 40 patients with AO type C pelvic fractures was performed. The mean age of the patients was 52.8 21.6 years. The study aimed to evaluate the functional outcomes and pain levels of patients surgically treated for unstable pelvic ring and sacral fractures using an ilio-iliac plate fixation in a minimally invasive technique. The minimum follow-up was 6 months. The patients were divided into two groups: low-energy trauma (n = 10) and high energy trauma (n = 30). The functional outcome was evaluated using the Majeed score. Pain levels were evaluated in the Numeric Rating Scale (NRS). The preoperative and postoperative blood hemoglobin levels and the changes in these values were evaluated. The data was processed, and a statistical analysis was performed. In the group of low-energy trauma, the mean NRS was 2.4 2.2. The group of high-energy trauma had a mean NRS of 2.8 2.7. In the group of low-energy trauma, the mean Majeed score was 78.0 17.7. The group of high-energy trauma had a mean Majeed score of 84.3 15.1. No statistical significance was found between the two groups of patients regarding pain level and functional outcome. There was a statistically significant difference in the pre-and postoperative blood hemoglobin values (p < 0.001). Preoperatively, the mean HGB value was 11.4 1.2 g/dl; postoperatively it dropped to a mean of 10.2 1.3 mg/dl. The mean difference in blood hemoglobin was 1.2 0.9 g/dl. Ilio-iliac plate fixation is a safe and technically easy method of pelvic fracture fixation. The study shows that functional outcomes are mainly good and excellent. The study demonstrated that the method of fixation can be used with good and predictive outcomes in high-energy pelvic trauma and osteoporotic fractures.